2008
DOI: 10.1007/s10653-008-9206-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and fractionation of mercury in soils from the Chatian mercury mining deposit, southwestern China

Abstract: Contents of total Hg and Hg fraction, organic matter, pH, grain size and chemical composition were measured to investigate the pollution characteristics and binding behavior of Hg in soils collected from the Chatian Hg mining deposit (CMD), southwestern China. The average concentration of Hg concentration in the CMD soils was 155 and 1,315 times higher than that in control soils and Chinese soils, respectively, suggesting that the CMD soils were heavily contaminated by the element. The finding was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 38 publications
(46 reference statements)
0
6
1
Order By: Relevance
“…Furthermore, significant differences (p \ 0.01) were found in hair As, Hg, and Se concentrations in the three areas. The proportion of residents' hair elements burden exceeded the upper limit of the normal content in China (Qin 2004): where the soil had a significantly higher concentration of As, Hg, and Se than the control area (Li et al 2009). When the hair element concentrations in our study are compared with the results from other research, the hair Hg level in CMM is lower than Wanshan (Li et al 2004) and Wuchuan (Li et al 2008) Hg mining areas in Guizhou, China, but the concentrations of hair Hg in CLM are higher than Chaihe (Wu et al 2007) lead/zinc mine area in Liaoning, China, and the hair burden of Cd, Pb, and As in CLM are at a lower range.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, significant differences (p \ 0.01) were found in hair As, Hg, and Se concentrations in the three areas. The proportion of residents' hair elements burden exceeded the upper limit of the normal content in China (Qin 2004): where the soil had a significantly higher concentration of As, Hg, and Se than the control area (Li et al 2009). When the hair element concentrations in our study are compared with the results from other research, the hair Hg level in CMM is lower than Wanshan (Li et al 2004) and Wuchuan (Li et al 2008) Hg mining areas in Guizhou, China, but the concentrations of hair Hg in CLM are higher than Chaihe (Wu et al 2007) lead/zinc mine area in Liaoning, China, and the hair burden of Cd, Pb, and As in CLM are at a lower range.…”
Section: Resultsmentioning
confidence: 96%
“…The coefficient between Cd-Pb, Cd-As, Pb-As, Se-As, and Se-Hg was positive and statistically significant. These correlations may be due to the natural geochemical background: both the CMM and CLM are typical low temperature hydrothermal combined Pb-Hg ore deposit with the presence of Cd, As, and Se as impurity elements (Li et al 2009). Previous studies also observed there were significant correlations between Pb-Cd, As-Cd, and Hg-Se in local soil, water and crops (Sun et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Extracting agents [14] Extracting agents [18] Extracting agents [19] Water has been shown to significantly increase the soluble mercury concentration in tailings, and to subsequently enhance the uptake of mercury by the species Brassica juncea Czern. [10].…”
Section: Fractionsmentioning
confidence: 99%
“…Many studies have shown the elevated concentration of toxic trace elements in the soils contaminated by various mining activities (e.g. Jung and Thornton, 1996;Bech et al, 1997;Li and Thornton, 2001;Liu et al, 2005;Li et al, 2009;Luo et al, 2012a). On the other hand, only a few studies have investigated the effect of W mining and smelting on contamination in the nearby soils (Jung et al, 2002;Jung, 2008;Ngoc et al, 2009;Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%